Computer aided engineering approach to the development of a lawnmower blade: a reverse engineering application to reduce noise levels / Trishel Gokool … [et al.] - Gokool, Trishel; Ali, Fahraz; Chowdary, Boppana V.; Kanchan, Kimberly (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2015)
Engineering seeks to improve the quality of life taking into consideration factors of safety and environment amongst others. The use of the lawnmower in landscape maintenance is quite common throughout various parts of the world with significant noise generated during its operation. This study seeks to develop a blade design via Computer Aided Engineering (CAE) that will reduce the noise intensity of the lawnmower while in use; thereby, reducing discomfort to the user and environs. The design of the blade was developed by utilization of engineering techniques such as reverse engineering (RE) and re-engineering (ReE) of an actual blade, coupled with computer aided design (CAD), for simulation of performance prior to the production of a prototype. The results of design simulation as well as from physical testing of the prototype were compared to determine the success of the CAE approach based on variations of both test results. The various procedures, from RE of the lawnmower blade and simulation of its improved design via CAD to the physical experimentation, proved that CAE was effective, since the prototype developed yielded a decrease in noise intensity when compared to the original lawnmower blade. Therefore, this study demonstrates the use of CAD and CAE in the development and enhancement of the blade design, as an effective approach, towards the improvement of quality of life based on reduced noise intensity.